Serological evidence of vector and parasite exposure in Southern Ghana: the dynamics of malaria transmission intensity - Badu, K.; Gyan, B.; Appawu, M.; Mensah, D.; Dodoo, D.; Yan, G.; Drakeley, C.; Zhou, G.; Owusu-Dabo, E.; Koram, K.A. (Parasites & Vectors, 2015)
Background: Seroepidemiology provides robust estimates for tracking malaria transmission when intensity is low and useful when there is no baseline entomological data. Serological evidence of exposure to malaria vectors and parasite contribute to our understanding of the risk of pathogen transmission, and facilitates implementation of targeted interventions. Ab to Anopheles gambiae salivary peptide (gSG6-P1) and merozoite surface protein one (MSP-1 19) reflect human exposure to malaria vectors and parasites. This study estimated malaria transmission dynamics using serological evidence of vector and parasite exposure in southern Ghana. Methods: Total IgG responses to both antigens in an age stratified cohort (<5, 5 – 14, >14) were measured from South-eastern Ghana. 295 randomly selected sera were analyzed from archived samples belonging to a cohort study that were followed at 3 consecutive survey months (n = 885); February, May and August 2009. Temporal variations in seroprevalence of both antigens as well as differences between the age-stratified cohorts were determined by χ 2 test with p < 0.05 statistically significant. Non-parametric repeated ANOVA – Friedman ’ s test was used to test differences in antibody levels. Seroprevalence data were fitted to reversible catalytic model to estimate sero-conversion rates. Results: Whereas parasite prevalence was generally low 2.4%, 2.7% and 2.4% with no apparent trends with season, seroprevalence to both gSG6-P1 and MSP1 19 were high (59%, 50.9%, 52.2%) and 57.6%, 52.3% and 43.6% in respective order from Feb. to August. Repeated measures ANOVA showed differences in median antibody levels across surveys with specific significant differences bet ween February and May but not August by post hoc Dunn ’ s multiple comparison tests for gSG6-P1. For MSP1 19 , no differences were observed in antibody levels between February and May but a significant decline was observe d from May to August. Seroconversion rates for gSG6-P1 increased by 1.5 folds from February to August and 3 folds for MSP1 19 . Conclusion: Data suggests exposure to infectious bites may be declining whereas mosquito bites remains high. Sustained malaria control efforts and surveillance are needed to drive malaria further down and to prevent catastrophic rebound. Operational fac tors for scaling up have been discussed.
Keywords: Anopheles gambiae; Salivary peptide; Malaria exposure; Seroprevalence; Seroconversion rate; Merozoite surface protein; Parasite prevalence